Annual Plan 1970-71 Part-I Explanatory Memorandum Government of Tripura - Planning Commission (Planning Commission, 1970)
Tripura which is now a Union Territory is a State of great antiquity . Once a Princely State , it claims to be the most ancient of all the farmer Princely States in India. It had been ruled by the Maharajas for an unbroken period of thirteen hundred years . It is a land of temples and tradition. Long hill ranges and deep forests have created a charming natural beauty . It is nice in its wealth of flora and fauna . Area of the Territory is about 10451 Sq. Kms. (length 183.5 Kms. and by width 112.7 Kms. ) - being not easily communicable .The Territory is generally regarded as one of the inaccessible areas.
Government of Tripura